Precocious Puberty in a 4-year-old Child with 46,XX Disorder of Sexual Development: A Case Report - Aini, Fitria Nugraha; Sutrisnani, Catur Suci (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Disorders of sex development (DSD) are congenital conditions in which there is a mismatch between chromosomal, gonadal, and phenotypic sex. Among 46,XX patients, the leading underlying disorder is congenital adrenal hyperplasia (CAH) secondary to 21-hydroxylase deficiency. Precocious puberty in 46,XX DSD is rarely documented, particularly in Indonesia. Case description: A four-year-old girl presented with atypical genitalia noted since birth with progressive enlargement resembling clitoromegaly. Physical examination revealed ambiguous genitalia, pubic hair development, and obesity. Laboratory results showed hyponatremia, markedly elevated estradiol, progesterone, and 17-hydroxyprogesterone, with suppressed gonadotropins. MRI demonstrated a uterus, ovary, cervix, vagina with clitoromegaly, and the absence of testicular tissue. Karyotyping confirmed 46,XX with negative SRY gene. Bone age was advanced, corresponding to an 11.5-year-old boy. Discussion: These findings indicated 46,XX DSD due to classical salt-wasting CAH with precocious puberty. In this patient, androgen excess may have induced early puberty through aromatization to estrogen. Pubertal development in DSD can be absent, delayed, incomplete, or prematurely triggered. Conclusion: This case highlights a rare presentation of precocious puberty in a child with 46,XX DSD. It underscores the inherent complexity of DSD, where misalignment between chromosomal, gonadal, and phenotypic sex creates substantial challenges for both diagnosis and clinical management.